Anal incontinence and Quality of Life in late pregnancy: a cross‐sectional study. (4th March 2014) - Johannessen, HH; Mørkved, S; Stordahl, A; Sandvik, L; Wibe, A
<x xml:space="preserve">Abstract</x> Objective To evaluate the association between different types of anal incontinence (AI) and Quality of Life (QoL) in late pregnancy. Design Cross‐sectional study. Setting Two maternity units in Norway 2009–2010. Population Primiparae aged 18 or over. Methods Participants answered questions about AI during the last 4 weeks of pregnancy on the St. Mark's score and impact of QoL in the Fecal Incontinence QoL score. Socioeconomic data were obtained from hospital records. Main outcome measures Self‐reported AI and impact on QoL. Results 1571 primiparae responded; 573 (37%) had experienced AI during the last 4 weeks of pregnancy. One third of the incontinent women reported reduced QoL in the domain 'Coping'. 'Women experiencing urgency alone reported markedly better QoL compared to any other AI symptoms. AI appeared to have the strongest impact on the domains 'Coping' and 'Embarrassment'. Depression was only associated with experiencing the combination of all three symptoms [odds ratio (OR) 13; 95%confidence interval (CI) 3.2–51]. Experiencing flatus alone weekly or more was associated with the highest impact on 'Embarrassment' (OR 20; 95%CI 6.4–61) compared with all other symptoms or combination of AI symptoms, except the combination of all three AI symptoms. Conclusions Between 3 and 10% of the primiparae in this material experienced AI to such a extent that it affected QoL. The greatest impact was seen in the QoL domain 'Coping'. These findings highlight the importance of an increased awareness of AI in late pregnancy among health professionals and the need to implement routine discussions about AI with expectant and new mothers.